Avifauna Diversity of Ternate Island for Geotourism Development in Aspiring Geopark - Dewi Ayu Anindita; Akhmad David K. Putra; Annisa Ramadani; Abdul Kadir Dahlan Arif; Harjul Ode Sudin (Global Review of Tourism and Social Sciences, 2025)
Ternate Island, part of the Wallacea region in North Maluku, harbors rich avifaunal diversity that holds ecological and tourism significance. This study assessed bird species diversity across ten sites to support geotourism initiatives in the Aspiring Ternate Geopark. Surveys were conducted from May 2023 to February 2024 using the MacKinnon List method, complemented by incidental observations and literature review. A total of 60 species from 35 families were recorded, including 11 species endemics to North Maluku and nine migratory taxa. The Columbidae family was the most represented, while the Endangered white cockatoo (Cacatua alba) highlighted the island’s conservation value. Species richness was highest at Ngade Lagoon (26 species) and lowest at Nukila Park (7 species). The Shannon–Wiener diversity index (H’ = 2.88) indicated moderate diversity. These findings provide essential baseline data for biodiversity management and demonstrate the potential of avifauna as a flagship resource for birdwatching-based geotourism development.